2016
DOI: 10.1002/1873-3468.12098
|View full text |Cite
|
Sign up to set email alerts
|

Small protein domains fold inside the ribosome exit tunnel

Abstract: Cotranslational folding of small protein domains within the ribosome exit tunnel may be an important cellular strategy to avoid protein misfolding. However, the pathway of cotranslational folding has so far been described only for a few proteins, and therefore, it is unclear whether folding in the ribosome exit tunnel is a common feature for small protein domains. Here, we have analyzed nine small protein domains and determined at which point during translation their folding generates sufficient force on the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 22 publications
2
90
0
Order By: Relevance
“…The linker is composed of 17 residues (130–146) that form two consecutive turns: one connecting the C-terminal α-helix which is a canonical α-turn (I140–K144), followed by a less well-ordered turn without hydrogen bonding (Figure 2a–d and Video 2). Protein folding events have been demonstrated to occur within the ribosomal exit tunnel (Holtkamp et al, 2015; Lin et al, 2012; Marino et al, 2016; Nilsson et al, 2015; Tu et al, 2014); (Bhushan et al, 2010b; Matheisl et al, 2015); Of those so far characterized, folding was shown to occur within the lower region of the tunnel, e.g. ADR1 (Nilsson et al, 2015) and within the vestibule at the periphery where the exit tunnel widens (Cabrita et al, 2016; Nilsson et al, 2017; Trovato and O'Brien, 2016; Tu et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The linker is composed of 17 residues (130–146) that form two consecutive turns: one connecting the C-terminal α-helix which is a canonical α-turn (I140–K144), followed by a less well-ordered turn without hydrogen bonding (Figure 2a–d and Video 2). Protein folding events have been demonstrated to occur within the ribosomal exit tunnel (Holtkamp et al, 2015; Lin et al, 2012; Marino et al, 2016; Nilsson et al, 2015; Tu et al, 2014); (Bhushan et al, 2010b; Matheisl et al, 2015); Of those so far characterized, folding was shown to occur within the lower region of the tunnel, e.g. ADR1 (Nilsson et al, 2015) and within the vestibule at the periphery where the exit tunnel widens (Cabrita et al, 2016; Nilsson et al, 2017; Trovato and O'Brien, 2016; Tu et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The narrowness and length of the exit tunnel (~20x100 Å) significantly constrains the most C-terminal residues of the nascent polypeptide chain to a small range of mostly extended or α-helical conformations [6,7]. The formation of bulky tertiary structure does not begin until the nascent chain is long enough to emerge from the exit tunnel (>35 aa), although there is evidence that the broader ‘vestibule’ near the end of the tunnel is wide enough to enable the nascent chain to fold back on itself to make some local tertiary structure contacts [8,9]. Synonymous codon substitutions near the 5′ end of a coding sequence are therefore unlikely to affect co-translational protein folding, as very little of the nascent chain has been translated and the portion that has been synthesized is constrained within the tunnel.…”
Section: Ribosome Structure and The Logistics Of Co-translational Promentioning
confidence: 99%
“…However, in the recent years many studies have shown in eukaryotes as well as in prokaryotes that protein folding already begins on the ribosome, while the C-terminal part of the polypeptide is still in the process of being extended at the peptidyl-transferase center. Furthermore, several recent studies have shown that the formation of secondary structures, such as α-helices, already begins within the ribosomal exit tunnel [8][9][10][11][12][13][14][15].…”
Section: Accepted Manuscriptmentioning
confidence: 99%